Evaluating the antibiotics' use on patients with chronic kidney failure in Al Iman General Hospital, Riyadh, Saudi Arabia - Al-Otaibi, Saqr Najer; Al-Baqami, Sami Zaki; Al-Enezi, Faisal Khalaf; Al-Otaibi, AbdulRahman Muhammad; Al-Otaibi, Ahmed Ghazai; Al-Nami, Mishaal Talaq (Journal of medical and pharmaceutical sciences, 2022)
Background: Antibiotics are one of the most widely utilized classes of medications for the treatment of infectious disorders. The application of antibiotics and can be seen as one of the most important things that hospitals accomplish since it contributes to maintaining a consistent level of living for a significant number of individuals. Aim of work: The purpose of this study was to investigate the appropriateness of the antibiotics.Patients and Methodology: About 48 cases who were being administered at the Al-Iman General Hospital located in Al-Riyadh, Saudi Arabia. This hospital treats a significant number of patients who suffer from chronic renal failure as well as a variety of infections. This study looked at a large number of cases to ensure that the evaluation included the appropriate indication, patient, medicine, and dose for each circumstance. This study looked backward at the medical records of people who had chronic renal failure and had been admitted to the hospital as inpatients. Results: The findings of the search and the evaluation revealed that the appropriate antibiotics were administered in as many as 32 of the cases (66.6%), that patients with chronic renal failure who met the appropriate criteria were present in 46 of the cases (95.8%), that the appropriate class of antibiotics was administered in 19 of the cases (34.7%), and that the appropriate dosage of antibiotics was administered in 18 of the cases (51.7%). All cases were discharged with a good and perfect health status.Conclusion: Using improper or prolonged usage of antibiotics is so dangerous in general and for patients with chronic kidney diseases specifically, so, antibiotics have the potential to produce nephrotoxicity in the kidneys, a person who has chronic renal failure should carefully consider whether or not they should take them.
Keywords: Al Iman general Hospital; antibiotics' use; chronic renal failure; Riyadh; Saudi Arabia